Atmosphere in urban design : a workplace ethnography of an architecture practice - Stenslund, Anette (Abingdon, Oxon : Routledge, 2023)
"This book offers an ethnographic exploration of the role that atmosphere plays in work processes undertaken within an urban design studio. It provides understandings of how architectural practices are fueled with atmosphere in various configurations throughout different design phases of selected projects for construction. From the outside architectural practices commonly appear well-ordered and carefully considered, established by proof and rationally justified. This book though poaches on architects' preserves in order to draw attention to features of unpredictability and uncertainty within the design phases. By opening up into the 'machinery room' of urban designers the goal is not to spoil the plaster saint cover of a 'starchitect' business, but to remind about the crucial value that pockets of doubt issuing questions rather than answers, open-mindedness instead of single-mindedness, play to the processes of design production and creativity. The book identifies these pockets as atmospheres enveloping the architectural practice"--
Keywords: Architecture and anthropology; Architectural practice; SCIENCE / Earth Sciences / Geography; SOCIAL SCIENCE / Human Geography